Non-Thermal Dielectric Barrier Discharge (DBD) Effects on Proliferation and Differentiation of Human Fibroblasts Are Primary Mediated by Hydrogen Peroxide. - Julian Balzer; Kiara Heuer; Erhan Demir; Martin A Hoffmanns; Sabrina Baldus; Paul C Fuchs; Peter Awakowicz; Christoph V Suschek; Christian Opländer (PLoS ONE)
The proliferation of fibroblasts and myofibroblast differentiation are crucial in wound healing and wound closure. Impaired wound healing is often correlated with chronic bacterial contamination of the wound area. A new promising approach to overcome wound contamination, particularly infection with antibiotic-resistant pathogens, is the topical treatment with non-thermal "cold" atmospheric plasma (CAP). Dielectric barrier discharge (DBD) devices generate CAP containing active and reactive species, which have antibacterial effects but also may affect treated tissue/cells. Moreover, DBD treatment acidifies wound fluids and leads to an accumulation of hydrogen peroxide (H2O2) and nitric oxide products, such as nitrite and nitrate, in the wound. Thus, in this paper, we addressed the question of whether DBD-induced chemical changes may interfere with wound healing-relevant cell parameters such as viability, proliferation and myofibroblast differentiation of primary human fibroblasts. DBD treatment of 250 μl buffered saline (PBS) led to a treatment time-dependent acidification (pH 6.7; 300 s) and coincidently accumulation of nitrite (~300 μM), nitrate (~1 mM) and H2O2 (~200 μM). Fibroblast viability was reduced by single DBD treatments (60-300 s; ~77-66%) or exposure to freshly DBD-treated PBS (60-300 s; ~75-55%), accompanied by prolonged proliferation inhibition of the remaining cells. In addition, the total number of myofibroblasts was reduced, whereas in contrast, the myofibroblast frequency was significantly increased 12 days after DBD treatment or exposure to DBD-treated PBS. Control experiments mimicking DBD treatment indicate that plasma-generated H2O2 was mainly responsible for the decreased proliferation and differentiation, but not for DBD-induced toxicity. In conclusion, apart from antibacterial effects, DBD/CAP may mediate biological processes, for example, wound healing by accumulation of H2O2. Therefore, a clinical DBD treatment must be well-balanced in order to avoid possible unwanted side effects such as a delayed healing process.